2012
DOI: 10.4067/s0718-58392012000200013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of using Quail Litter Biochar on Soybean (Glycine max L. Merr.) Production

Abstract: Biochars can be used as soil amendments for improving soil properties and crop yield. The objective of this research was to study the plant growth, yield, yield components, and seed quality, including nutrients and heavy metals (Pb, Cd, and Hg), in the soybean plant (Glycine max [L.] Merr.) and soil. The experiment was conducted from September 2010 to January 2011 in a greenhouse located in the Dan Khun Thot District, Nakhon Ratchasima Province, Thailand. The research comprised six treatments with four replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 30 publications
1
15
0
2
Order By: Relevance
“…In soybean, the adequate plant nutrition is essential for enhance the pod set, which requires adequate availability of nutrients and assimilates in soybean plants [22]. These results are consistent with other studies, which it was observed a positive and high correlation between organic and mineral fertilizer use on number of pods per plants [21] [26].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In soybean, the adequate plant nutrition is essential for enhance the pod set, which requires adequate availability of nutrients and assimilates in soybean plants [22]. These results are consistent with other studies, which it was observed a positive and high correlation between organic and mineral fertilizer use on number of pods per plants [21] [26].…”
Section: Resultssupporting
confidence: 82%
“…When in suitable amount, biochar use can enhance agro ecosystems. Converting agricultural wastes into a useful soil amendment that holds carbon and makes soils more fertile, avoiding the deforestation and improving the food security [20] [21]. Through the response surfaces is observed that the best dose combination was the application of 5.49 Mg•ha −1 of either organic amendments combined with 200 kg•ha −1 of the mineral fertilizer; in order to obtain 2792; 2796 and 3672 kg•ha −1 of soybean grains obtained by the farmyard manure, biochar and poultry litter use, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The highest pH was found in poultry biochar followed by pine needle biochar, bagasse biochar and mixed biochar treated soils. The study of Suppadit et al (2012) also found an increase in pH and EC. An increase in soil pH by increasing biochar application rate might be due to the presence of alkali elements (Ca, Mg and Na) and the presence of -OH ions in biochar (Danish et al, 2015).…”
Section: Results and Discussion:-mentioning
confidence: 90%
“…Biochar significantly affected the number of viable achenes (NVA) and production of achenes per plant (PROD). According to Suppadit et al (2012) biochar had a significant effect on soy production components. There is also a significant effect of the interaction between the factors D × B for PROD (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…According to Banerjee et al (2014) It is observed that, although the fertilization with biochar reduced NVA values ( Figure 3B), the dose of 400 g/pot (19.62 g/plant) promoted an increase in the PROD of 16.72% in relation to the plants which were not fertilized with biochar (16.34 g/plant). According to Suppadit et al (2012) the application of 98.6 g/pot of biochar promoted a higher yield of soybean seeds. According to Tagoe et al (2008) the combination of 11.4 g/pot of biochar with 410 mg kg -1 of K increased the yield of soybeans and cowpea, respectively, of 53 and 185% in relation to the control (without fertilization).…”
Section: Resultsmentioning
confidence: 99%